The The Impact of Exercise on Quality of Life, Physical Health, and Mental Health in Type 2 Diabetes Mellitus Patients: Meta-Analysis - Bertha Sylvester Maingu; Wardhatul Livia; Isna Andriani; Bhisma Murti; Elsa Tursina (Masters Program in Public Health, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a prevalent metabolic disorder that is common on a global scale. Effective management in addition to medication involves implementing lifestyle modifications, including regular exercise. This study aimed to analyze and estimate the impact of exercise on improving quality of life, physical health, and mental health in type 2 diabetes mellitus patients.Subjects and Method: This was a meta-analysis study using the PICO model which includes; P= type 2 diabetes mellitus patients; I= exercise; C= no exercise; and O= quality of life, physical health, and mental health. The articles obtained were from 2 databases, namely PubMed and ScienceDirect. Keywords used include “exercise” OR “physical activity” AND “quality of life” OR “physical health” OR “mental health” AND “type 2 diabetes mellitus” AND “randomized control trial”. The inclusion criteria of articles were a randomized control trial study design, publication year from 2018 to 2023, full-text, English language, and reported mean and standard deviation values. Data was analyzed using the PRISMA diagram and the Review Manager 5.3 application.Results: This meta-analysis consisted of 13 articles originating from Canada, Denmark, Egypt, Ghana, Iran, Saudi Arabia, Spain, Taiwan, Turkey, and USA. The total sample size was 755 type 2 diabetes mellitus patients. Exercises improved the quality of life (SMD= 0.66; CI 95%= 0.20 to 1.11; p= 0.005); physical health (SMD= 0.91; CI 95%= 0.53 to 1.29; p= 0.001) and mental health (SMD= 0.82; CI 95%= 0.25 to 1.39; p= 0.005) in type 2 diabetes mellitus patients.Conclusion: Exercise carried out regularly and measurably improves the quality of life, physical health, and mental health in type 2 diabetes mellitus patients. Keywords: Exercise, quality of life, physical health, mental health, type 2 diabetes mellitus.